Essentials of clinical mycology - Kauffman, Carol A. (Springer, 2011)
Essentials of Clinical Mycology gives a comprehensive overview of the field of clinical mycology. It is written for clinicians who care for patients who have fungal infections. Each of the major systemic fungal infections is discussed in regard to mycology, pathogenesis, epidemiology, clinical manifestations, diagnosis, and treatment. The increasing antifungal armamentarium is described in depth, and separate chapters review increasing antifungal resistance and the use of combination therapy. A section is devoted to high-risk patients who have received a stem cell or solid organ transplant, are neutropenic, or have HIV infection and who are at high risk for developing invasive fungal infections.